Avoidability of hospital deaths and association with hospital-wide mortality ratios: retrospective case record review and regression analysis. (14th July 2015) - Hogan, Helen; Zipfel, Rebecca; Neuburger, Jenny; Hutchings, Andrew; Darzi, Ara; Black, Nick
Abstract : Objectives To determine the proportion of avoidable deaths (due to acts of omission and commission) in acute hospital trusts in England and to determine the association with the trust's hospital-wide standardised mortality ratio assessed using the two commonly used methods - the hospital standardised mortality ratio (HSMR) and the summary hospital level mortality indicator (SHMI). Design Retrospective case record review of deaths. Setting 34 English acute hospital trusts (10 in 2009 and 24 in 2012/13) randomly selected from across the spectrum of HSMR. Main outcome measures Avoidable death, defined as those with at least a 50% probability of avoidability in view of trained medical reviewers. Association of avoidable death proportion with the HSMR and the SHMI assessed using regression coefficients, to estimate the increase in avoidable death proportion for a one standard deviation increase in standardised mortality ratio. Participants 100 randomly selected hospital deaths from each trust. Results The proportion of avoidable deaths was 3.6% (95% confidence interval 3.0% to 4.3%). It was lower in 2012/13 (3.0%, 2.4% to 3.7%) than in 2009 (5.2%, 3.8% to 6.6%). This difference is subject to several factors, including reviewers' greater awareness in 2012/13 of orders not to resuscitate, patients being perceived as sicker on admission, minor differences in review form questions, and cultural changes that might have discouraged reviewers from criticising other clinicians. There was a small but statistically non-significant association between HSMR and the proportion of avoidable deaths (regression coefficient 0.3, 95% confidence interval −0.2 to 0.7). The regression coefficient was similar for both time periods (0.1 and 0.3). This implies that a difference in HSMR of between 105 and 115 would be associated with an increase of only 0.3% (95% confidence interval −0.2% to 0.7%) in the proportion of avoidable deaths. A similar weak non-significant association was observed for SHMI (regression coefficient 0.3, 95% confidence interval −0.3 to 1.0). Conclusions The small proportion of deaths judged to be avoidable means that any metric based on mortality is unlikely to reflect the quality of a hospital. The lack of association between the proportion of avoidable deaths and hospital-wide SMRs partly reflects methodological shortcomings in both metrics. Instead, reviews of individual deaths should focus on identifying ways of improving the quality of care, whereas the use of standardised mortality ratios should be restricted to assessing the quality of care for conditions with high case fatality for which good quality clinical data exist.